ARTICLE 25 INCOME TAX ASPECTS OF TAXPAYER UNDER CERTAIN EMPLOYERS LAW 36 OF 2008 - Shofiana, Dina Eka (Entrepreneur, 2012)
Abstract The business world is now experiencing a very rapid progress. Among other factors affecting the opening lines of international trade, technological sophistication, a more flexible business rules to be triggered by a change in consumption patterns. Indonesia is also experiencing a change in the business world in the country is experiencing significant growth, particularly the real sector. thriving outlets, shops, kiosks, cafes, grocery store or mini seiiring with the rapid growth of shopping malls such as, mall, shopping center, where the longer growing numbers. Types of goods sold even more diverse. Various reasons that makes people to be involved in the business world, such as ease of starting, does not require a large capital and specialized expertise, vast place, to ease in matters of taxation. Perpetrators in the business of trading is commonly referred to as retail traders. In the context of income tax, the scope of the retailers provided for in Article 1 of Regulation Number 2 Director General of Taxation (DG) Tax Number PER-32/PJ./2010, which is an individual retailers who make sales of goods either wholesale or retail and delivery services through a place. In tax treatment, as retailers attach individual taxpayer Specific Employers (WPOPPT). Use of designation "Entrepreneur Specific" is intended to emphasize the specificity of the tax treatment for retail merchants.. Keywords: Retail merchants, Income Tax Abstrak Dunia bisnis kini mengalami kemajuan yang sangat pesat. Diantara faktor-faktor lain yang mempengaruhi garis pembukaan perdagangan internasional, kecanggihan teknologi, aturan bisnis yang lebih fleksibel untuk dipicu oleh perubahan pola konsumsi. Indonesia juga mengalami perubahan dalam dunia bisnis di Tanah Air mengalami pertumbuhan yang signifikan, khususnya sektor riil. berkembang outlet, toko, kios, kafe, toko kelontong atau mini seiiring dengan pesatnya pertumbuhan pusat perbelanjaan seperti, mal, pusat perbelanjaan, di mana semakin banyak lagi. Jenis barang yang dijual lebih beragam. Berbagai alasan yang membuat orang untuk terlibat dalam dunia bisnis, seperti kemudahan awal, tidak memerlukan modal yang besar dan keahlian khusus, tempat yang luas, untuk memudahkan dalam hal perpajakan. Pelaku dalam bisnis perdagangan sering disebut pedagang ritel. Dalam konteks pajak penghasilan, ruang lingkup pengecer diatur dalam Pasal 1 Peraturan Nomor 2 Direktur Jenderal Pajak (Ditjen) Pajak Nomor PER-32 / PJ. / 2010, yang merupakan pengecer perorangan yang melakukan penjualan barang baik grosir atau eceran dan pengiriman jasa melalui tempat. Dalam perlakuan pajak, sebagai pengecer melampirkan Wajib Pajak Pengusaha Tertentu individu (WPOPPT). Penggunaan sebutan "Pengusaha Tertentu" dimaksudkan untuk menekankan kekhususan perlakuan pajak untuk pedagang eceran. Kata kunci: pedagang eceran, Pajak Penghasilan.